Neutral effects of turbidity across a gradient of vegetation density on the predation of juvenile mandarin fish (Siniperca chuatsi). Issue 5 (16th October 2019) - Li, Wei; Zhang, Tanglin; Hicks, Brendan J.; Zhang, Chaowen; Li, Zhongjie; Liu, Jiashou
Abstract: Mandarin fish Siniperca chuatsi is a widespread piscivorous species in lakes of the Yangtze River basin. However, their wild population has drastically declined, and survival and growth rates of stocked populations are low. Anthropogenic activities have reduced submersed vegetation and increased turbidity in lakes containing S. chuatsi, thus, we hypothesize that reduced submersed vegetation and increased turbidity could inhibit the feeding efficiency of juvenile S. chuatsi, subsequently reducing their growth and survival. To test this hypothesis, we experimentally examined the effects of a range of vegetation density and turbidity on predation of S. chuatsi . Laboratory predation trials were performed with a common prey fish Carassius auratus offered simultaneously to S. chuatsi in clear or turbid water under five different levels of vegetation density (0, 20, 40, 80, and 120 stems/m 2 ). The total prey consumption per day (in 24 hr) by S. chuatsi on C. auratus was significantly affected by vegetation density, with the consumption positively linearly related with increased vegetation density. The total prey consumption was unaffected by turbidity. Prey size selection was not significantly influenced by vegetation density or turbidity. These results indicate that turbidity does not appear to negatively affect the predation of S. chuatsi, but a reduction of vegetation can negatively influence feeding induced by decreased predation efficiency, and hence might hinder survival and growth.